Digital reminiscence app co‐created by people living with dementia and carers: Usability and eye gaze analysis. (15th June 2021) - Boyd, Kyle; Bond, Raymond; Ryan, Assumpta; Goode, Deborah; Mulvenna, Maurice
Abstract: Background: This research reports on a pilot study that examined the usability of a reminiscence app called 'InspireD' using eye tracking technology. The InspireD app is a bespoke digital intervention aimed at supporting personalized reminiscence for people living with dementia and their carers. The app was developed and refined in two co‐creation workshops and subsequently tested in a third workshop using eye tracking technology. Intervention: Eye tracking was used to gain insight into the user's cognition since our previous work showed that the think‐aloud protocol can add to cognitive burden for people living with dementia while also making the test more unnatural. Results: Results showed that there were no barriers to using a wearable eye tracker in this setting and participants were able to use the reminiscence app freely. However, some tasks required prompts from the observer when difficulties arose. While prompts are not normally used in usability testing (as some argue the prompting defeats the purpose of testing), we used 'prompt frequency' as a proxy for measuring the intuitiveness of the task. There was a correlation between task completion rates and prompt frequency. Results also showed that people living with dementia had fewer gaze fixations when compared to their carers. Carers had greater fixation and saccadic frequencies when compared to people living with dementia. This perhaps indicates that people living with dementia take more time to scan and consume information on an app. A number of identified usability issues are also discussed in the paper. Patient or Public Contribution: The study presents findings from three workshops which looked at user needs analysis, feedback and an eye tracking usability test combined involving 14 participants, 9 of whom were people living with dementia and the remaining 5 were carers.